2020
DOI: 10.53986/ibjm.2020.0058
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Aspirin as Breakthrough Drug for COVID-19: A Narrative Review

Abstract: Introduction: Aspirin has justifiably been called the first miracle drug. In this article, we highlight the history of Aspirin, a novel mechanism of action, and its use in cardiovascular and other diseases. Also included is a brief statement of emerging new applications. Objective: We highlight principal mechanisms by which Aspirin inhibits acute inflammation and alters platelet-biology; therefore, hypothesized that Aspirin might prove highly beneficial as a novel therapeutic drug for combating severe acute in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 102 publications
0
4
0
Order By: Relevance
“…In addition, in another study, researchers examined the anti-inflammatory role of salicylates and the progression of coronary plaque and its volume (Hauser et al 2016). Studies have shown that acetylsalicylic acid attenuates the activation of inflammatory cytokines dependent on the NF-κB signalling pathway and, on the other hand, can improve respiratory function in patients with SARS-CoV-2 infection (Taha et al 2020;Alegbeleye et al 2020). Considering the effects of salicylates in various studies, in a large clinical trial, its effects in reducing various inflammatory cytokines caused by cytokine storm and therapeutic effects in COVID-19 can be investigated.…”
Section: Nf-kappa Bmentioning
confidence: 99%
“…In addition, in another study, researchers examined the anti-inflammatory role of salicylates and the progression of coronary plaque and its volume (Hauser et al 2016). Studies have shown that acetylsalicylic acid attenuates the activation of inflammatory cytokines dependent on the NF-κB signalling pathway and, on the other hand, can improve respiratory function in patients with SARS-CoV-2 infection (Taha et al 2020;Alegbeleye et al 2020). Considering the effects of salicylates in various studies, in a large clinical trial, its effects in reducing various inflammatory cytokines caused by cytokine storm and therapeutic effects in COVID-19 can be investigated.…”
Section: Nf-kappa Bmentioning
confidence: 99%
“…It was postulated that combating thrombus formation through different pathways, such as antiplatelet or direct thrombin inhibitors, could potentially help overcome the cytokine storm associated with COVID-19 patients. 22 Interestingly, we observed a twofold increase in the all thrombosis cases in aspirin recipients. This observation could potentially be explained by the fact that these patients, due to their underlying risk, may require an additional new therapeutic approach or higher doses of aspirin may be warranted.…”
Section: Discussionmentioning
confidence: 59%
“…Aspirin decreases platelet turnover and prevents thrombus formation [ 116 ]. Aspirin mitigates severe COVID-19 complications [ 117 ]. Thus, it can be expected that, coupled with other effective drugs, aspirin could reduce death rate in critically ill COVID-19 patients.…”
Section: Possible Causes Of Covid-19 Severitymentioning
confidence: 99%